Sutures modified by incorporation of chlorhexidine and cinnamaldehyde: anti-Candida effect, bioavailability and mechanical properties - Raphael Cavalcante COSTA; Yuri Wanderley CAVALCANTI; Ana Maria Gondim VALENÇA; Leopoldina de Fátima Dantas de ALMEIDA (Universidade Estadual Paulista, 2019)
Abstract Introduction Antimicrobial sutures are a therapeutic alternative for the control of oral infections. Objective Incorporate Chlorhexidine (CHX) and Cinnamaldehyde (CN) in sutures and evaluate the anti-Candida effect, release of antimicrobials and mechanical properties. Material and method Silk (S) and Polyglactin 910 (P) sutures were aseptically sectioned (20 mm) and immersed for incorporation in 0.12% CHX, 0.4% CN and 0.9% saline solutions under stirring for 60 minutes (n = 10 / group). Suspensions of 500 μL of Candida albicans (ATCC 90028/ 1 × 106 CFU/mL) were used to evaluate fungal adhesion after the 48 h period at 37°C. The release of CLX and CN were evaluated at 0, 24 and 48 hours (n=3/group) by UV-VIS spectrophotometer (275 nm). The tensile strength and displacement (n=5/group) were evaluated after incorporation (30 mm/min, 50N). Data were analyzed by Anova and Tukey (α = 5%). Result No anti-Candida effect was observed on S and P sutures incorporated with CLX and CN (p>0.05). However, progressive release was verified up to 48 after treatment with CLX (S = 0.075 / P = 0.073 μg/mL) and CN (S = 35.33 /P= 5.72 μg/mL). There was a decrease in tensile strength in S (CLX = 9.9 / CN = 9.9 N) and P (CLX = 14.4 / CN = 15.5 N) (p<0.05). No differences were observed for the displacement for S (CLX = 19.3 / CN=20.7 mm) and P (CLX = 16.2 / CN=15.8 mm) (p>0.05). Conclusion The incorporation of CLX and CN did not have a positive effect on the biological and mechanical properties of the sutures evaluated.